Utilização da espectroscopia PIXE na avaliação do mecanismo de biossorção dos íons Cu²+, Zn²+ e Cd²+ pela macrófita Egeria densa - Santos, Gustavo Henrique Fidelis dos (2012)
The main objective of this study was to evaluate the types of biosorption mechanisms involved in the removal of copper, zinc and cadmium divalent ions by dead Egeria densa macrophyte biomass. Batch adsorption experiments, consisting of mixtures of 0.3 g biomass and 50 mL metal solution were performed at initial pH 5, and under constant temperature (50 oC) and shaking conditions. The PIXE analytical technique was applied to determine the metal concentration in aqueous and solid phases. All PIXE measurements were performed at the Ion Beam-based Material Analysis Laboratory of the Physics Institute of the São Paulo University. Preliminary to adsorption experiments, the point of zero charge assigned to E. densa biosorbent was determined to be at a 5.0-6.5 pH value range. From metal speciation diagrams, the Cu, Zn, Cd and Ca divalent ions are expected to be majorities below the pH values of 5, 6, 8, and 10, respectively, whereas above these pH regions other metal compounds are mainly expected. As confirmed by measured pH values of 5.0 ± 0.2 at all experiments of adsorption and desorption, E. densa biosorbent submerged in each metal solution has exhibited zero net electrical charge on its surface, indicating that the removals of Cu²+, Zn²+, and Cd²+ and the desorption of these metal ions should be mainly performed by the ion exchange mechanism. According to the mass balance analysis performed for each metal adsorption experiment, the ion exchange process was confirmed to be the main mechanism for the metal removal and desorption by the E. densa biosorbent. At pH value of 5 the E. densa biosorbent surface shows a behavior of ion exchanger.